LEADERSHIP AS A MANDATORY ELEMENT IN THE DEVELOPMENT OF NON-GOVERNMENTAL ORGANIZATIONS AND THEIR INTERACTION WITH BUSINESS STRUCTURES - RUDNICHENKO, Yevhenii; HARBUZIUK, Oleksandra; HAVLOVSKA, Nataliia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores the peculiarities of the functioning of non-governmental organizations from the perspective of the influence of leaders on their development processes and interactions with external stakeholders. The theoretical foundation for understanding leadership and its role in organizational development is defined. Key theoretical concepts related to the formation of connections between various management structures are presented. The distinctions between leadership and management are outlined. The study establishes the dependence of the effective functioning of a non-governmental organization on the presence of leaders. The necessity for interaction between non-governmental organizations and business entities is substantiated in the context of creating a synergistic effect for their development.The author proposes a definition of "leadership" as the ability of an individual to influence the behavior of others and/or their own behavior by understanding and harmonizing individual and group interests, inspiring and directing toward goal achievement. It is a process that integrates self-regulation, goal orientation, management, motivation, interaction, cooperation, decision-making, and adaptation to change for the development of an organization or one's own enterprise.The necessity of stimulating leadership qualities among members of non-governmental organizations is emphasized to integrate positive experiences of such organizations’ interaction with international donors into the business sector. The feasibility of developing joint projects and programs at the regional and national levels is identified. Major risks of non-governmental organizations ceasing operations amid global socio-economic changes are highlighted. The article justifies the need to seek alternative long-term funding sources for non-governmental organizations.
Keywords: leadership; non-governmental organizations; development; business; interaction; enterprise management; partnership